UPAYA MENINGKATKAN PRESTASIBELAJARIPA-FISIKA MELALUI PENERAPAN STRATEGI PEMBELAJARAN INKUIRITERBIMBING PADA SISWA KELAS VHI DI MTsN - Kirno Suwanto (Jurnal Penelitian Ilmu Pendidikan, 2010)
This research is aim to know : 1) to implementation of guided inquiry learning strategy for for the increasing of students achievement's IPA-Fisika, 2) to increasing of students achievement's IPA-Fisika throug implementation of guided inquiry learning strategy. The research subject of this class action research is all of the students of who sit on class VIII STsN 1 Ngemplak Boyolali, there are consist of 36 students. The data is collected with the technique test and observation. The technique test is to know the student achievement while the observation is to know the students attention, response, and activeness. The data is analyzed by utilization student comparative description analysis and T-test. The result of this research are: 1) implementation of guided inquiry learning strategy for for the increasing of students achievement's IPA-Fisika by step: a) phase of presentation of internal issue form of spread sheet student, b) discussion of guidance, c) activity of descovery, d) final discussion, e) to make the conclusion and follow-up..2) improvement of achievement learn of IPA-Fisika at interest elementary wake up the side space arch to pass guided inquiry learning strategy to show at improvement attainment of achievement learn the student at cycle I and H at cycle I from 36 student obtain to sum up value counted 217,5 average value 6,024 with standard deviasi 1,003. at cycle II: get to sum up value counted 252, average value 7,00 with standard deviation 0,802. From result obtain of achievement learn at cycle I and n analysis by using test t. From result calculation the show that to 4,933, ttabie= 1,67 at level signifikansi 0,05 with db=70. So that inferential that applying guided inquiry learning strategy can to improve achievement learn of IPA-Fisika. Keyword: Guided Inquiry Learning Strategy, Achievement's IPA-Fisika